Self-reported morbidity and health service utilization in rural Tamil Nadu, India. (July 2016) - Dodd, Warren; King, Nia; Humphries, Sally; Little, Matthew; Dewey, Cate
Abstract: In Tamil Nadu, India, improvements have been made toward developing a high-quality, universally accessible healthcare system. However, some rural residents continue to confront significant barriers to obtaining healthcare. The primary objective of this study was to investigate self-reported morbidity, health literacy, and healthcare preferences, utilization, and experiences in order to identify priority areas for government health policies and programs. Drawing on 66 semi-structured interviews and 300 household surveys (including 1693 individuals), administered in 26 rural villages in Tamil Nadu's Krishnagiri district, we found that the prevalence of self-reported major health conditions was 22.3%. There was a large burden of non-communicable and chronic diseases, and the most common major morbidities were: connective tissue problems (7.6%), nervous system and sense organ diseases (5.0%), and circulatory and respiratory diseases (2.5%). Increased age and decreased education level were associated with higher odds of reporting most diseases. Low health literacy levels resulted in individuals seeking care only once pain interfered with daily activities. As such, individuals' health-seeking behaviour depended on which strategy was believed to result in the fastest return to work using the fewest resources. Although government facilities were the most common healthcare access point, they were mistrusted; 48.8% and 19.2% of respondents perceived inappropriate treatment protocols and corruption, respectively, at public facilities. Conversely, 93.3% of respondents reported high treatment cost as the main barrier to accessing private facilities. Our results highlight that addressing the chronic and non-communicable disease burdens amongst rural populations in this context will require health policies and village-level programs that address the low health literacy and the issues of rural healthcare accessibility and acceptability. Highlights: Chronic and non-communicable diseases were commonly reported in this setting. Demographic factors were associated with self-reported morbidity categories. Health literacy and beliefs shaped health-seeking behaviour. Barriers existed in accessing quality public or private healthcare. Perceptions of rural public healthcare were poor despite recent improvements.